2021
DOI: 10.1021/acsomega.1c04317
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Heat Storage Performance of a Na2HPO4·12H2O System via Introducing Multiwalled Carbon Nanotubes

Abstract: The hydrated salt disodium hydrogen phosphate dodecahydrate (DHPD, Na 2 HPO 4 •12H 2 O) has a suitable phase transition temperature and high latent heat of phase transition. Still there are problems such as supercooling, phase separation, and low thermal conductivity. In this paper, DHPD, sodium carboxymethyl cellulose (CMC), aluminum oxide (Al 2 O 3 ), and poly-(vinylpyrrolidone) (PVP) are used to configure DHPD-CAP to suppress supercooling and phase separation successfully. Multiwalled carbon nanotubes (MWCN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Jia's group [80] developed a CVD method and successfully synthesized aligned CNTs (a-CNTs) by using propylene as the carbon source (Figure 5c), which decomposed on vermiculite-supported catalysts in a fluidized bed reactor. Compared with randomly In addition to the enhancement of thermal conductivity, Ding et al [83] reported that MWCNTs together with SCMC altered the phase change temperature and the fusion enthalpy of DHPD. In contrast to pure DHPD, which exhibited two melting peaks at 33.42 • C and 45.85 • C, the DHPD-SCMC-MWCNT composites effectively suppressed the phase separation of DHPD and the formation of low-grade salt Na 2 HPO 4 •7H 2 O, showed a single melting peak, and increased the latent heat enthalpy by 36.19%.…”
Section: Hydrated Salt-cnt Compositesmentioning
confidence: 99%
“…Jia's group [80] developed a CVD method and successfully synthesized aligned CNTs (a-CNTs) by using propylene as the carbon source (Figure 5c), which decomposed on vermiculite-supported catalysts in a fluidized bed reactor. Compared with randomly In addition to the enhancement of thermal conductivity, Ding et al [83] reported that MWCNTs together with SCMC altered the phase change temperature and the fusion enthalpy of DHPD. In contrast to pure DHPD, which exhibited two melting peaks at 33.42 • C and 45.85 • C, the DHPD-SCMC-MWCNT composites effectively suppressed the phase separation of DHPD and the formation of low-grade salt Na 2 HPO 4 •7H 2 O, showed a single melting peak, and increased the latent heat enthalpy by 36.19%.…”
Section: Hydrated Salt-cnt Compositesmentioning
confidence: 99%
“…Moreover, polymer thickeners do not provide shape stabilization or prevent leakage of molten PCMs (Figure S1). In contrast, covalently crosslinked polymer gels, which also often require large polymer amounts (5%–60% by weight), provide shape stabilization (Figure S1). However, the permanent nature of the crosslinks renders these materials irreversible, making filling and removal from thermal energy storage modules impossible.…”
Section: Introductionmentioning
confidence: 99%